Inequalities Involving Conformable Approach for Exponentially Convex Functions and Their Applications - Jun-Feng Li; Saima Rashid; Jia-Bao Liu; Ahmet Ocak Akdemir; Farhat Safdar (Journal of Function Spaces)
In the article, we present several Hermite–Hadamard-type inequalities for the exponentially convex functions via conformable integrals. As applications, we give new inequalities for certain bivariate means.